Inspection of maleic anhydride in starch powder using line-scan hyperspectral Raman chemical imaging technique - Qin, Jianwei; Kim, Moon S.; Chao, Kuanglin; Bellato, Lisa; Schmidt, Walter F.; Cho, Byoung-Kwan; Huang, Min (International Journal of Agricultural and Biological Engineering, 2018)
Excessive use of maleic anhydride (MAN) in starch production is potentially harmful for consumers’ health. This study presents a macro-scale Raman chemical imaging method for detection and quantification of MAN particles mixed in starch powder. MAN was mixed into corn starch at eight concentration levels from 50 ppm to 6400 ppm (w/w). Each mixture was put in a sample holder with a 150 mm×100 mm area and a 2 mm depth to create a large surface and a thin layer of the powdery sample for inspection. A 30 W 785 nm line laser was projected on the sample surface, from which hyperspectral images were obtained by a line-scan Raman imaging system with a spatial resolution of 0.2 mm. Fluorescence signals generated by laser-sample interactions were eliminated by a mathematical baseline correction method. A unique Raman peak was selected at 1839 cm−1 for the MAN detection, at which single-band fluorescence-corrected images were extracted from the mixture of each concentration and used to generate chemical images for MAN detection and mapping. The MAN detection limit was estimated at 100 ppm based on the Raman imaging measurement results. Pixel concentrations of the MAN in the chemical images were found linearly correlated with mass concentrations of the MAN particles in the starch powder, suggesting the Raman chemical imaging method has the potential for quantitative detection of the MAN in the starch-MAN mixtures. Keywords: Raman spectroscopy, chemical imaging, starch, adulteration, food authentication DOI: 10.25165/j.ijabe.20181106.4339 Citation: Qin J W, Kim M S, Chao K L, Bellato L, Schmidt W F, Cho B-K, et al. Inspection of maleic anhydride in starch powder using line-scan hyperspectral Raman chemical imaging technique. Int J Agric & Biol Eng, 2018; 11(6): 120–125.